Food-feed systems in Asia - review - Devendra, C.; Sevilla, C.; Pezo, Danilo A. (2001)
This review paper discusses the relevance and potential importance of food-feed systems in Asian agricultural systems, and in particular the role and contribution of legumes to these systems. A food-feed system is one that maintains, if not increases, the yield of food crops, sustains soil fertility, and provides dietary nutrients for animals. It involves a cropping pattern within which the feed crop has many beneficial effects without competing for land, soil nutrients and water with the food crops. The agricultural environment is described with reference to the priority agro-ecological zones and prevailing mixed farming systems in Asia. Within these systems, animal production is severely hampered by critical feed shortages which can however, be alleviated by the integration of suitable leguminous forages into the cropping systems. The review also focuses on the role and potential importance of leguminous forages in terms of biodiversity, their uses in farming systems, beneficial effects on animal performance, and draws attention to six case studies in different countries that clearly demonstrate many benefits of developing such food-feed systems. Considerable opportunities exist for widening the use of forage legumes in the development of systems with several complementary advantages (e.g. fenceline, cover crops, fodder banks, forage source and erosion control) to improve the development of sustainable crop-animal systems in Asia.